Comparative study of the crystallographic expansion of GSC and LSC porous electrodes. Issue 3 (12th June 2021) - Kivi, Indrek; Nurk, Gunnar; Korjus, Ove; Möller, Priit; Aruväli, Jaan; Lust, Karmen; Lust, Enn
Abstract: Characteristics of the porous Gd0.15 Sr0.85 CoO3−δ and La0.6 Sr0.4 CoO3−δ cathodes were compared using the data measured at different electrode potentials and oxygen partial pressures. The electrochemical high‐temperature in situ XRD (HT‐XRD) method combined with electrochemical impedance spectroscopy has been used. The response of the crystallographic parameters and impedance values on the changes of electrode potential has been discussed. Reversible changes of the lattice parameters for both cathodes, slower for Gd0.15 Sr0.85 CoO3−δ compared with La0.6 Sr0.4 CoO3−δ, were observed depending on temperature ( T ), electrode potential ( E ), and oxygen partial pressure ( p O2 ). The crystallographic parameters are determined by the vacancy formation kinetics as well as by vacancy formation energy in/at the cathode grain structure. Calculated impedance data were fitted to the experimental data and characteristics were obtained in context of crystallographic changes of the cathode materials studied.